INNOVATION IN GREEN TECHNOLOGY - USM CONTINUES TO DRIVE SUSTAINABILITY - MPRC, Pusat Media & Perhubungan Awam (2017)
SUNGAI PETANI, KEDAH, 1 February 2017 – Being a sustainability-led university, Universiti Sains Malaysia (USM) continues its drive for excellence in sustainable practices by introducing the cementless concrete with a low carbon footprint, which is ready for commercialisation. It is the research outcome using green technology by a lecturer from USM School of Housing, Building and Planning (HBP), Dr. Cheah Chee Ban.